Pelatihan Pembibitan Tanaman Hutan Bagi Kelompok Pemuda di Desa Daru - Zeth Patty; Ebedly Lewerissa; Ariance Yeane Kastanja (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
The training activities are targeted at Youth group in Daru Village, with the main problem is a lack of knowledge about forest plant nursery techniques. The target to be achieved is to increase the knowledge and skills of young people in the supply of plant seeds. The method used is counseling and training aimed at improving youth skills in forestry seedling nursery techniques. The results of the implementation of the activities show that the training activities have been able to produce the expected output that is to provide knowledge and skills for youth, as well as have encouraged youth in Daru Village to replant forest areas independently.